2003
DOI: 10.1046/j.1601-5215.2003.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets of lithium action

Abstract: Lithium is an effective drug for both the treatment and prophylaxis of bipolar disorder. However, the precise mechanism of lithium action is not yet well understood. Extensive research aiming to elucidate the molecular mechanisms underlying the therapeutic effects of lithium has revealed several possible targets. The behavioral and physiological manifestations of the illness are complex and are mediated by a network of interconnected neurotransmitter pathways. Thus, lithium's ability to modulate the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 271 publications
0
23
0
Order By: Relevance
“…Our finding was similar to the Petrini et al [13] findings showing that lithium at therapeutic doses can ameliorate vincristine neuropathy. It is widely accepted that lithium robustly protects neurons against excitotoxicity mediated by NMDA receptors [9,30]. Boyle et al [31] showed that glutamate can significantly prevent or ameliorate sensorimotor neuropathy induced by either vincristine or paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding was similar to the Petrini et al [13] findings showing that lithium at therapeutic doses can ameliorate vincristine neuropathy. It is widely accepted that lithium robustly protects neurons against excitotoxicity mediated by NMDA receptors [9,30]. Boyle et al [31] showed that glutamate can significantly prevent or ameliorate sensorimotor neuropathy induced by either vincristine or paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, microtubules interfering agents like vincristine or paclitaxel may disturb non-neoplastic cells such as nerves and finally cause apoptosis. Hence, peripheral neuropathy is one of the most frequent side effects of these two drugs that usually result in dose modification and changes in the treatment plan [5][6][7][8].As a mood stabilizer, lithium is commonly prescribed for bipolar disorders, and although its mechanism of action remains unknown, it is well established that lithium exerts some of its therapeutic effects through G-protein-coupled pathway, glycogen synthase kinase-3 (GSK3b), inositol monophopsphate and nitric oxide-dependent pathways and augmentation of serotonin function in the central nervous system [9,10]. Previous studies have reported that lithium has neuroprotective effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used for the treatment of bipolar disorders for almost a halfcentury (Corbella and Vieta, 2003). Lithium ion has a neuroprotective effect on brain tissue.…”
Section: J Lithium Ion and Carbamazepinementioning
confidence: 99%
“…It affects multiple cellular signaling pathways in the brain [1] and has neurotrophic and neuroprotective effects [2]. Studies utilizing anatomical region-of-interest [3,4] and cortical pattern matching [5] methods, as well as neurochemical imaging [6], demonstrated detectable brain changes related to lithium treatment in bipolar patients.…”
Section: Introductionmentioning
confidence: 99%